Differentiation-associated ISG expression of NK cells in chronic viral infection - Franziska Keller; Robert Lorenz Chua; Timo Trefzer; Katharina Jechow; Liane Bauersfeld; Fabian Beier; Sagar; Özlem Sogukpinar; Giuseppe Rusignuolo; Marta Rizzi; Roland Eils; Andreas Pichlmair; et al. (iScience)
Summary: Natural killer (NK) cell responses are modulated by type-I interferons (IFNs) in viral infection. Chronic hepatitis C virus (HCV) infection, marked by robust IFN signatures, shows NK cells with reduced cytokine release but heightened cytotoxicity. Comparable alterations occur in chronic hepatitis B virus (HBV) infection even without a pronounced IFN milieu, implying additional regulatory layers. We analyzed NK cells from healthy donors and patients with chronic HBV or HCV and found conserved expression patterns of interferon-stimulated genes (ISGs) such as IFITM3, IRF1, IFIT2, and ISG20 that correlated with NK cell differentiation state. These genes are governed by fate-determining transcription factors, including ETS1, FLI1, and Eomes, and appear to be constitutively expressed rather than driven by persistent IFN exposure. Network analysis suggested that NK cell ISGs participate not only in antiviral defense but also in processes such as transport and metabolism, underscoring their role in shaping NK responses during health and chronic viral infection.